2007
DOI: 10.1007/s00248-007-9313-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Rhizospheric Bacteria Diversity Along an Altitudinal Gradient in South American Puna Grassland

Abstract: Rhizospheric soil samples were taken from Puna native grasses along an altitudinal gradient. Biodiversity of arbuscular mycorrhizal fungi (AMF) and associated bacteria was analyzed considering altitude and grasses photosynthetic pathways (metabolic type C3, C4). Cultivation-dependent approaches were applied to obtain further information about the phylogeny of the dominating cultivable aerobic-heterotrophic bacteria communities present in rhizospheric soil samples. In average, the bacterial count ranged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
63
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 52 publications
16
63
5
1
Order By: Relevance
“…For example, spore abundance has been found to decrease with increasing elevation (Gai et al 2012) but also to pass through a maximum at an intermediate altitude (Li et al 2014;Coutinho et al 2015). AMF species richness furthermore has been reported as not affected (Li et al 2014) or decreasing (Lugo et al 2008;Gai et al 2012) with increased elevation or has been observed to peak at intermediate altitudes in an altitude gradient (Coutinho et al 2015). In contrast, the present study has indicated no correlation between AMF spore number and species richness with increasing altitude (Fig.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…For example, spore abundance has been found to decrease with increasing elevation (Gai et al 2012) but also to pass through a maximum at an intermediate altitude (Li et al 2014;Coutinho et al 2015). AMF species richness furthermore has been reported as not affected (Li et al 2014) or decreasing (Lugo et al 2008;Gai et al 2012) with increased elevation or has been observed to peak at intermediate altitudes in an altitude gradient (Coutinho et al 2015). In contrast, the present study has indicated no correlation between AMF spore number and species richness with increasing altitude (Fig.…”
Section: Discussioncontrasting
confidence: 79%
“…We disagree with the conclusion of Gai et al (2012) that a general pattern of AMF diversity and abundance over gradients in elevation can be detected worldwide. Our results along with recently published studies (Li et al 2014;Coutinho et al 2015) contrast with the patterns found by others (Lugo et al 2008;Schmidt et al 2008), thus suggesting that the variation in spore abundance and species richness over altitude gradients is, in fact, site-dependent and that variable conditions among those common to mountain environments -e. g., low temperatures, rainfall and moisture regimes, and frostinginfluence the abundance and richness of AMFs in different ways.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Throughout this paper, we used the recent revision of Scutellospora by Oehl et al (2008) since it is more practical for spore identification. Lugo et al (2008) also found ten AMF species in the Puna highlands (Argentina), and notably two species (A. spinosa and D. biornata) were in common.…”
Section: Resultsmentioning
confidence: 87%